2020
DOI: 10.1111/jnu.12601
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Cultural Competence of Nurses Providing Nursing Care in Slovakia

Abstract: The cultural competence of healthcare providers is a professional imperative and has been linked to increased health disparities (Prosen, 2015). In health care, cultural competence has been defined in multiple ways. Described by Schim and Doorenbos (2010) as an integration of personal cultural diversities, awareness, and sensitivity into everyday clinical practice, the American Nurses Association (2015) characterizes cultural competence as a process through which nurses deliver culturally congruent care for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
3
9
2
Order By: Relevance
“…The findings of this scoping review suggest that appropriate educational training can increase the cultural competence of nurses. These findings are supported by Cicolini et al (2015) , Yilmaz et al (2017) , Červený et al (2020) , and Antón-Solanas et al (2021) . Marja and Suvi (2021) report that simulations allow the integration of cultural elements into different vocational training and deepen the overall understanding of patient-centered cultural practices among simulation participants.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The findings of this scoping review suggest that appropriate educational training can increase the cultural competence of nurses. These findings are supported by Cicolini et al (2015) , Yilmaz et al (2017) , Červený et al (2020) , and Antón-Solanas et al (2021) . Marja and Suvi (2021) report that simulations allow the integration of cultural elements into different vocational training and deepen the overall understanding of patient-centered cultural practices among simulation participants.…”
Section: Discussionsupporting
confidence: 55%
“…This general tool evaluates any qualitative methodology. It has 10 questions asking the researcher to assess whether appropriate research methods were used and whether the findings were presented meaningfully ( Červený et al, 2020 ; Long et al, 2020 ). The results of the quality assessment are presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Lin et al (2021) found that cultural competence education acquired in nursing school has no influence on the cultural competence of registered nurses, but does seem to have an influence on pre-graduate nursing students [ 11 ]. Another study shows that nurses who are older and have received prior diversity training exhibit significantly higher levels of cultural competence [ 12 ]. These findings indicate that the assessment of Austrian nurses’ cultural competence and the identification of factors that influence this competence can help researchers and healthcare professionals to develop coherent interventions and to improve culturally competent care.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Council of Nurses (ICN) [ 25 ], patients have the right to culturally and clinically appropriate care in order to ensure best patient outcomes. However, preparing nurses to provide safe and culturally competent nursing care requires significant education and training [ 26 , 27 ]. Thus, the means of providing safe and culturally competent quality care should be central components of nursing education [ 7 , 28 ].…”
Section: Introductionmentioning
confidence: 99%